Prevalence and factors associated with suicidal behavior among trans women in Rio de Janeiro, Brazil. - Ricardo de Mattos Russo Rafael; Emilia Moreira Jalil; Paula Mendes Luz; Cristiane Regina Vinissius de Castro; Erin C Wilson; Laylla Monteiro; Michelle Ramos; Ronaldo Ismério Moreira; Valdiléa Gonçalves Veloso; Beatriz Gilda Jegerhorn Grinsztejn; Luciane de Souza Velasque (PLoS ONE, 2021)
Background Trans women face disproportionate burden of adverse health outcomes, including mental health issues. Very little is known about suicidal behavior among trans women in low- and middle-income settings, such as Brazil. We aimed to estimate the prevalence of lifetime suicidal behavior and to identify its associated factors among Brazilian trans women. Methods This was a cross-sectional study conducted among 345 trans women living in Rio de Janeiro, Brazil. We examined the prevalence of suicidal behavior (ideation and suicide attempt) and its associated factors using stepwise backward Poisson regression analysis with robust variance. Results Suicidal ideation was present among 47.25% of participants, and the prevalence of lifetime suicide attempt was 27.25%. Trans women with prior physical violence perpetrated by a family member had significantly higher prevalence of suicidal ideation (adjusted prevalence ratios [aPR]1.37), whereas those who reported sex work had lower prevalence ratio of suicidal ideation (aPR 0.76). Suicide attempt was significantly associated with living alone (aPR 1.48), physical violence by a casual partner (aPR 1.92), and sexual violence by a family member (aPR 1.69). Depression was significantly associated with both outcomes (aPR 1.90 for suicidal ideation and aPR 2.21 for suicide attempt). Conclusion Suicidal behavior prevalence rates among Brazilian trans women were alarming and directly linked to violence and poor mental health. Effective mental health and public health policies addressing violence against trans women are urgently needed to prevent suicidal behavior among this highly vulnerable population.